Synergistic activity of BET inhibitor MK-8628 and PLK inhibitor Volasertib in preclinical models of medulloblastoma. (31st March 2019) - Han, Youjia; Lindner, Sven; Bei, Yi; Garcia, Heathcliff Dorado; Timme, Natalie; Althoff, Kristina; Odersky, Andrea; Schramm, Alexander; Lissat, Andrej; Künkele, Annette; Deubzer, Hedwig E.; Eggert, Angelika; et al.
Abstract: Medulloblastoma is the most prevalent central nervous system tumor in children. Targeted treatment approaches for patients with high-risk medulloblastoma are needed as current treatment regimens are not curative in many cases and cause significant therapy-related morbidity. Medulloblastoma harboring MYC amplification have the most aggressive clinical course and worst outcome. Targeting the BET protein BRD4 has significant anti-tumor effects in preclinical models of MYC -amplified medulloblastoma, however, in most cases these are not curative. We here assessed the therapeutic efficacy of the orally bioavailable BRD4 inhibitor, MK-8628, in preclinical models of medulloblastoma. MK-8628 showed therapeutic efficacy against in vitro and in vivo models of MYC -amplified medulloblastoma by inducing apoptotic cell death and cell cycle arrest. Gene expression analysis of cells treated with MK-8628 showed that anti-tumor effects were accompanied by significant repression of MYC transcription as well as disruption of MYC-regulated transcriptional programs. Additionally, we found that targeting of MYC protein stability through pharmacological PLK1 inhibition showed synergistic anti-medulloblastoma effects when combined with MK-8628 treatment. Thus, MK-8628 is effective against preclinical high-risk medulloblastoma models and its effects can be enhanced through simultaneous targeting of PLK1. Highlights: MK-8628 is a small molecule BRD4 inhibitor. MK-8628 is active in preclinical models of medulloblastoma in vitro and in vivo . MK-8628 treatment leads to apoptosis and cell cycle arrest in medulloblastoma cells. Treatment with MK-8628 leads to disruption of MYC-driven transcriptional programs. Combining PLK1 inhibitors with MK-8628 exhibits synergistic anti-tumor activity.